Utilisation analysis and comparison for multimedia wireless networks. (21st May 2008) - Zhang, Yuhong; Salari, Ezzatollah
In this paper, we consider a homogeneous wireless multimedia system with both priority and non-priority calls. The resources of the system are either as the nominal channels assigned evenly to each of the coved cells or reserved in the control centre exclusively for priority calls. Different classes of calls may request different bandwidths for a satisfactory connection. We investigate how the utilisation depends on the channel allocation schemes and whether a buffer space affects the performance of the system in terms of the utilisation of the system. Our observation is expected to provide technical guidance for the design of channel allocation of multimedia wireless systems.